Pan-genomic analyses identify key Helicobacter pylori pathogenic loci modified by carcinogenic host microenvironments. Issue 10 (18th September 2017) - Noto, Jennifer M; Chopra, Abha; Loh, John T; Romero-Gallo, Judith; Piazuelo, M Blanca; Watson, Mark; Leary, Shay; Beckett, Amber C; Wilson, Keith T; Cover, Timothy L; Mallal, Simon; Israel, Dawn A; et al.
Abstract : Objective: Helicobacter pylori is the strongest risk factor for gastric cancer; however, the majority of infected individuals do not develop disease. Pathological outcomes are mediated by complex interactions among bacterial, host and environmental constituents, and two dietary factors linked with gastric cancer risk are iron deficiency and high salt. We hypothesised that prolonged adaptation of H. pylori to in vivo carcinogenic microenvironments results in genetic modification important for disease. Design: Whole genome sequencing of genetically related H. pylori strains that differ in virulence and targeted H. pylori sequencing following prolonged exposure of bacteria to in vitro carcinogenic conditions were performed. Results: A total of 180 unique single nucleotide polymorphisms (SNPs) were identified among the collective genomes when compared with a reference H. pylori genome. Importantly, common SNPs were identified in isolates harvested from iron-depleted and high salt carcinogenic microenvironments, including an SNP within fur (FurR88H). To investigate the direct role of low iron and/or high salt, H. pylori was continuously cultured in vitro under low iron or high salt conditions to assess fur genetic variation. Exposure to low iron or high salt selected for the FurR88H variant after only 5 days. To extend these results, fur was sequenced in 339 clinical H. pylori strains. Among the isolates examined, 17% (40/232) of strains isolated from patients with premalignant lesions harboured the FurR88H variant, compared with only 6% (6/107) of strains from patients with non-atrophic gastritis alone (p=0.0034). Conclusion: These results indicate that specific genetic variation arises within H. pylori strains during in vivo adaptation to conditions conducive for gastric carcinogenesis.